Effects of physical exercise on physical and mental health in older adults with gait disorders: a systematic review - Xu, Fan; Soh, Kim Geok; Chan, Yoke Mun; Soh, Kim Lam; Bai, Xiao Rong; Deng, Nuan Nuan; Liu, Huan Ge (Elsevier, 2025)
The benefits of physical exercise are well-known, but there is limited research on its effects on the physical and mental health of elderly individuals with gait disorders. This review aims to evaluate the impact of physical exercise on these outcomes. A literature search was conducted, retrieving studies published from inception to November 2024 in databases such as PubMed, Scopus, Web of Science, ProQuest, and SPORTDiscus. Fifteen randomized controlled trials (RCTs) were included in the review. The results indicate that physical exercise improves both physical health (gait, balance, mobility, reduce fall rate) and mental health (Qality of life [QoL] cognitive function, anxiety levels, and Activities-Specific Balance Confidence [ABC]) in older adults with gait disorders. Of the 15 studies, 10 reported positive effects on both physical and mental outcomes, while the remaining five studies showed either no effect or a lack of positive results. The interventions evaluated included Tai Chi (TC), Tango, aerobic training (AT), resistance training (RT), combined training (CT), virtual reality (VR), resistance training plus standard pharmacological treatment (RTG + pharmacological treatment), high-speed treadmill training, brisk walking, and multimodal exercise program (MEP). Notably, there are six items of TC intervention. Most interventions lasted for 12 weeks with sessions conducted twice a week, each lasting between 30 and 60 minutes. Additionally, limited studies (one per indicator) assessed strength, functional gait assessment (FGA), and center of pressure (COP), indicating a need for more research in these areas. This review concludes that physical exercise is effective in improving physical and mental health outcomes in older adults with gait disorders, with TC emerging as the most commonly used and beneficial intervention.